(untitled) (Research, Society and Development, 2020)
The formation of an economic orchard of yellow passion fruit depends on the vigor of the seedlings, which is expressed based on the growth and nutritional status of the plants. The objective of this study was to determine the growth and nutritional status of yellow passion fruit seedlings in response to individual and combined actions of liming, NPK and micronutrients, whose treatments were subjected to a randomized block design with five replications. The characteristics evaluated during the conduct of the experiment were height, stem diameter and number of leaves. At the end, the production of dry masses of stem, leaf and roots, and the aerial part: root relationship were determined; and the chemical composition regarding the levels of N, P, K, Ca, Mg, Cu, Fe, Mn and Zn in the aerial part of the passion fruit. NPK fertilization stimulated shoot growth, but restricted the production of yellow passion fruit seedling roots. Limestone and micronutrient applications had the opposite effects of NPK fertilization, that is, they stimulated the formation of roots, but decreased the aerial part of seedlings. Liming induced low concentrations of Fe, Mn and Zn. The growth of seedlings was quite accentuated over the period evaluated, which suggests care with fertilization in order to avoid nutritional restrictions.